Quality of Educational Services and Experiential Marketing on Student Satisfaction and Its Implications on Student Trust Evidence - Wasito, Wasito; Baihaqi, Muhammad Iqbal (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: This study aims to find out, examine, and obtain the results of an analysis of the quality of educational services, experiential marketing, student satisfaction, and student trust to determine the magnitude of the influence of the quality of educational services and experiential marketing on student satisfaction and its implications for trust. Methodology: The method used is descriptive and verification. Determining the sample size in the study used the Slovin formula where a sample of 378 respondents was obtained.Finding: The descriptive study found that the quality of educational services and experiential marketing was perceived as good, student satisfaction was perceived as satisfied, perceived trust was sufficient. Meanwhile, using SEM, the results show that there is an effect of the quality of educational services and experiential marketing on student satisfaction both partially and simultaneously, there is an effect of student satisfaction on student trust.Conclusion: The quality of educational services for students of the management study program accredited A at Private University in Bandung Metropolitan is perceived as good, this is based on the results of the average score of respondents' answers being in the good category.